2016
DOI: 10.1007/s11306-016-0967-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat-treatment on the stability and composition of metabolomic extracts from the earthworm Eisenia fetida

Abstract: Environmental metabolomics studies employing earthworms as sentinels for soil contamination are numerous, but the instability of the metabolite extracts from these organisms has been minimally addressed. This study evaluated the efficacy of adding a heat-treatment step in two commonly used extraction protocols (Bligh and Dyer and D2O phosphate buffer) as a pre-analytical stabilization method. The resulting metabolic profiles of Eisenia fetida were assessed using principal component analysis and NMR spectral ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Earthworms are sensitive to contaminants, found in most terrestrial ecosystems, and are essential ecological engineers responsible for degrading plant matter and providing soil aeration; thus, they are a clear choice for environmental monitoring . Many studies have used metabolomics to examine the impact of heavy metals, industrial contaminants, and pesticides on the earthworm metabolome. , Though whole-worm extracts are typically used for these studies, ,, alternatively, several articles have examined metabolic perturbations in earthworm coelomic fluid (CF). CF is an aseptic biofluid that fills the earthworm body cavity (i.e., coelom) between the gut and muscle tissue and is a central location of metabolism, immunity, hepatocytic function, nutrient storage, and excretion . Metabolite analysis in the CF was chosen for these studies because CF extrusion is noninvasive, nonlethal, and requires minimal sample preparation and thus is advantageous over whole-worm extracts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earthworms are sensitive to contaminants, found in most terrestrial ecosystems, and are essential ecological engineers responsible for degrading plant matter and providing soil aeration; thus, they are a clear choice for environmental monitoring . Many studies have used metabolomics to examine the impact of heavy metals, industrial contaminants, and pesticides on the earthworm metabolome. , Though whole-worm extracts are typically used for these studies, ,, alternatively, several articles have examined metabolic perturbations in earthworm coelomic fluid (CF). CF is an aseptic biofluid that fills the earthworm body cavity (i.e., coelom) between the gut and muscle tissue and is a central location of metabolism, immunity, hepatocytic function, nutrient storage, and excretion . Metabolite analysis in the CF was chosen for these studies because CF extrusion is noninvasive, nonlethal, and requires minimal sample preparation and thus is advantageous over whole-worm extracts .…”
Section: Introductionmentioning
confidence: 99%
“…4 Many studies have used metabolomics to examine the impact of heavy metals, industrial contaminants, and pesticides on the earthworm metabolome. 2,5 Though wholeworm extracts are typically used for these studies, 2,5,6 alternatively, several articles have examined metabolic perturbations in earthworm coelomic fluid (CF). 7−10 CF is an aseptic biofluid that fills the earthworm body cavity (i.e., coelom) between the gut and muscle tissue and is a central location of metabolism, immunity, hepatocytic function, nutrient storage, and excretion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, it has been previously noted that some invertebrate species, like the earthworm, have high enzymatic content [19]. In metabolomics-based studies of earthworms, it was shown that heating whole-body metabolite extracts was beneficial for improving metabolite and total lipid stability [19,20], thus making them ideal candidates for this examination. The current study was performed both to highlight the potential lipid changes that occur immediately following animal sacrifice, and to propose heat treatment as a means to reduce this change.…”
mentioning
confidence: 99%